Fire Resistance of Building Structures and Fire Protection Materials: Bibliometric Analysis - Marina Victorovna Gravit; Irina Leonidovna Kotlyarskaya; Olga Alexandrovna Zybina; Dmitriy Alexandrovich Korolchenko; Zhmagul Smagulovich Nuguzhinov (Fire)
Scientometric analysis using the Scopus database and VosViewer program identified the critical directions of development of this or that field to identify promising technologies and to understand how these achievements affect the practice of design and construction. According to the analytics, the average number of articles per year on the topic of structural fire resistance and flame retardants increased by 18% compared to the previous period, and according to preliminary data, the trend will continue in 2024. Among the most cited papers, studies on composite materials and polymers dominate. Among the most productive researchers in the field of flame retardancy of materials are Hu, Yuan (54 papers), Wang, WeiYong (47 papers), and Jiang, Jian (39 papers). According to Scopus, research papers on this topic have been published in 2175 sources. The leading journal in terms of the number of published papers is Fire Safety with 250 publications, but journals such as Fire and Buildings of MDPI Publishing are strongly increasing the pace. Chinese researchers are actively studying various aspects of fire resistance of materials and have published 40% of all papers. Keyword analysis revealed a lack of papers on calculation of fire resistance of structures with fire protection means, calculation of fire resistance of composite structures, and 3D-printed structures compared to the number of articles on the reliability (strength calculation) of building structures.